PERAN PENGELOLAAN KAS TERHADAP LIKUIDITAS PADA CV. PARULIAN SOJUANGAN PANGGABEAN (PSP) GROUP DAERAH KECAMATAN BADIRI - Silalahi, Radika; Hutagalung, Jeniusman Ahmad; Simatupang, Sahat (Lembaga Pengembangan Kinerja Dosen, 2023)
Liquidity issues are important in maintaining the smooth operation of the company as well as in short-term and emergency needs as well as the growth function (investment) to develop owned assets in accordance with the expectations desired by the company. Information about budgeted cash flows can produce relevant information, because from this cash flow it can be known the need for the company's operations from the source of the recipient. Given the large number of cash receipts and disbursements managed, a list is needed that contains all cash inflows and cash outflows presented in the form of a cash flow statement. The results of the discussion concluded that cash management plays a role in the liquidity of CV. PSP Group, this can be proven from the results of research by calculating liquidity with the Current Ratio, Cash Ratio, and Quick Ratio, where the calculation results for 1 year, namely from January to December 2021 the calculation results for the liquidity ratio are > 1 as much as 75%, where with the existence of good cash management will have a positive impact, which means the application of cash management at CV. PSP Group is better, on company liquidity and financial conditions with a liquidity ratio of < 1 of 25%, which means that future conditions need to be improved in cash management to make it even better because there are still conditions that cash management in 2021 is not liquid or in the sense that CV. From July to September, the PSP Group was unable to pay its current debts in a timely manner, which resulted in obstacles to the company's payment of employee salaries and other important company expenses.